Magnetic resonance imaging in respiratory medicine - Safavi, Shahideh (2019)
At present, pulmonary function tests (PFTs) and computed tomography (CT) are the two principal investigation modalities used in the management of chronic respiratory diseases. However, PFTs provides no spatial functional data, whilst the use of CT is hampered due to the risks associated with ionising radiation. Magnetic resonance imaging (MRI) is a non-invasive and non-ionising imaging modality. Conventional MRI, however, is of little value in imaging the lungs due to poor image quality. New MRI modalities have been developed over the past two decades to enhance the applicability of MRI in respiratory medicine. I undertook a series of studies with the broad aim of defining the practicalities, advantages, and disadvantages of using MRI in the management of patients with respiratory disease.